Climate-induced drying of Lake Azzurro (Central Italian Alps): impacts and future projections - Ceppi, Alessandro; Taborelli, Giulia; Gambini, Enrico; Marchioni, Mariana; Becciu, Gianfranco; Dresti, Claudia (Frontiers in Earth Science, 2025)
Alpine lakes have proven particularly sensitive to climate change, especially to fluctuations in air temperature and precipitation. Such variations can affect the ecosystem services provided by mountain lakes, like freshwater supply for local population and regulation of nutrient cycling that supports biodiversity, impacting on a vital resource which serves as essential habitat for a wide range of plant and animal species as well. This study aims to examine the impacts of climate variability on Lake Azzurro, a small lake located in the municipality of Campodolcino in the Central Italian Alps. The lake follows a natural seasonal cycle, typically characterized by a reduction of water level from late summer to mid-autumn, followed by reappearance in late spring. However, since the early 2000s, it has experienced prolonged dry periods, specifically in 2005–2006, 2018, and 2022–2023. To investigate the relationship between lake’s existence and climatological variables, weather data from a nearby meteorological station were analyzed. This was followed by an impact assessment based on high-resolution climate projections (RCP 4.5 and RCP 8.5 scenarios) derived from Centro Euro-Mediterraneo sui Cambiamenti Climatici (CMCC) models, with horizontal resolutions of 2.2 and 8 km, extending through the end of the century. The results suggest an increasing frequency of drying events that could lead to a progressive loss of this ecologically and culturally significant lake. Such a decline would have substantial implications for the ecosystem services it provides to both the local community and the broader region. The findings underscore an urgency for raising public awareness of the lake’s vulnerability, a call for the development of comprehensive mitigation strategies, such as improved water resource management, biodiversity conservation, and the promotion of sustainable land-use practices within the lake’s catchment area.